Influence of biological intensification on the balance of sod-podzolic soil nutrient elements in field crop rotations - L. M. Kozlova; F. A. Popov; E. N. Noskova; E. V. Svetlakova (Аграрная наука Евро-Северо-Востока)
The studies were carried out in the Kirov region on sod-podzolic sandy loam soil in a long-time stationary experiment established in 1976. The article provides data (2010-2017) on four fallow-grain-grass crop rotations with various types of fallows, annual and perennial legumes (25-50 %), intercrops (12.5-37.5 %). The purpose of the studies is to compare the influence of some biologization techniques in eight-field crop rotations on the change in soil fertility and the balance of nutritional elements of sod-podzolic sandy loam soil. It is found that the application of low doses of mineral fertilizers (N30P30K30) and various types of green manure crops per rotation has significantly increased the content of mobile phosphorus in the arable soil layer (by 39-46 mg/kg). According to grouping the provision of soils with phosphorus, the content of this element passed into the «high provision» group. The content of exchangeable potassium in the soil remained in the «increased» provision group. In the control crop rotation with clean fallow at a minimum supply of nutrients with mineral fertilizers and root-stubble residues, the balance of nitrogen, phosphorus and potassium was created negative at the intensity of less than 100 %. The replacement of clean fallow for cropped and green manure fallows, as well as the introduction of intermediate cruciferous crops into the crop rotation structure contributed to the positive balance of nitrogen (250.2-484.3 kg/ha) with the intensity of 124-150 %. The biologization factors used in crop rotations favored the creation of a positive phosphorus balance (12.5-148.1 kg/ha) with the optimal intensity of 117-163 % and a positive potassium balance (128.9-395.8 kg/ha) with the intensity above the optimal value of 116-148 %. The most advantageous in terms of productivity and ensuring a positive balance of nutritional elements is crop rotation with two green manure fallows and sowing of stubble and hay cruciferous crops in three fields.